Digital Cultures in the Americas - Gómez Cruz, Edgar (2020)
More than two decades have passed since the publication of two seminal books in the study of digital cultures in Latin America. First was Ciberculturas en la era de las máquinas inteligentes (Piscitelli, 1995), published in Buenos Aires. Piscitelli (1995) sided with authors such as Eric Havelock, Marshall McLuhan, and Walter Ong by considering the advent of the Internet as the cause for a major “cognitive metamorphosis” in humanity (p. 21). “Never have the possibilities offered by technology been as big as they are today, and never have these possibilities been so ignored, hidden, or squandered,” he wrote in one of the opening paragraphs (p. 20). (All translations are our own.) Then, one year later, came La nueva alfombra mágica: Usos y mitos de Internet, la red de redes (Trejo Delarbre, 1996), published in Mexico City and Madrid. The book, as its author noted, had as its primary purpose to make “the resources of cyber-communication useful for the development of Latin American societies” (1996, p. 17). Both books, pioneers in questioning the importance of an emerging Internet, signaled the beginning of a Latin American interest in digital technologies from the perspectives of the social sciences and humanities. They were both largely exploratory works that sought to make sense, for the first time in the region, of the opportunities and challenges entailed by the rise of this emerging technology.